Maternal Sepsis: A Review of National and International Guidelines - Stephens, Angela J.; Chauhan, Suneet P.; Barton, John R.; Sibai, Baha M. (American Journal of Perinatology, 2021)
Sepsis is a life-threatening syndrome caused by the body's response to infection. The Global Maternal Sepsis Study (GLOSS) suggests sepsis plays a larger role in maternal morbidity and mortality than previously thought. We therefore sought to compare national and international guidelines for maternal sepsis to determine their consistency with each other and the Third International Consensus for Sepsis and Septic Shock (SEPSIS-3). Using Cochrane Database of Systematic Reviews, PubMed, Google Scholar, and organization Web sites, we identified seven guidelines on maternal sepsis in the English language—The American College of Obstetricians and Gynecologists, Society for Maternal-Fetal Medicine, Royal Australian and New Zealand College of Obstetricians and Gynaecologists, Society of Obstetric Medicine of Australia and New Zealand, Royal College of Obstetricians and Gynaecologists, Royal College of Physicians of Ireland Institute of Obstetricians and Gynaecologists, and World Health Organization. Guidelines were reviewed to ascertain the commonality and variation, if any, in definitions of maternal sepsis, tools and criteria utilized for diagnosis, obstetric warning systems used, as well as evaluation and management of maternal sepsis. These variables were also compared with SEPSIS-3. All guidelines provided definitions consistent with a version of the SEPSIS, although the specific version utilized were varied. Clinical variables and tools employed for diagnosis of maternal sepsis were also varied. Evaluation and management of maternal sepsis and septic shock were similar. In conclusion, national and international maternal sepsis guidelines were incongruent with each other and SEPSIS-3 in diagnostic criteria and tools but similar in evaluation and management recommendations.Key Points
Keywords: sepsis; maternal sepsis; sepsis in pregnancy; obstetric warning systems; SEPSIS-3; maternal mortality